The Chemical Bond I 100 Years Old and Getting Stronger - Mingos, D. Michael P. (Structure and Bonding, 2016)
D. Michael P. Mingos -- The Chemical Bond: Lewis and Kossel's Landmark Contribution Dietmar Stalke -- Charge Density and Chemical Bonding Fu Kit Sheong, Wen-Jie Chen, and Zhenyang Lin -- Lewis Description of Bonding in Transition Metal Complexes Gernot Frenking and Markus Hermann -- Gilbert Lewis and the Model of Dative Bonding Jean-Yves Saillard and Jean-François Halet-- Structure and Bonding Patterns in Large Molecular Ligated Metal Clusters Vaida Arcisauskaite, Xiao Jin, José M. Goicoechea, and John E. McGrady -- Electronic Properties of Endohedral Clusters of Group 14 Shengda Ding and Michael B. Hall -- The Rich Structural Chemistry Displayed by the Carbon Monoxide as a Ligand to Metal Complexes.